PERILAKU NASABAH BERDASARKAN KINERJA CUSTOMER RELATIONSHIP MANAGEMENT SEBAGAI DAMPAK DARI KOMPETENSI SUMBER DAYA MANUSIA, MUTU PELAYANAN BANK DAN TEKNOLOGI PERBANKAN TERHADAP KEPUASAN NASABAH (Studi pada Nasabah Bank Kota Tangerang) - Dudung Hadiwijaya (Universitas Muhammadiyah Tangerang, 2020)
The purpose of the study is to analyze how much influence human resource competence, banking service quality and banking technology on customer satisfaction and the impact on customer behavior based on customer relationship management (CRM) performance at Bank in Tangerang City. The sample of research is 110 customers at Bank in Tangerang City. The sampling technique uses convenience sampling. Data collection using questionnaire. The method used in this research is the method of verification. To determine the effect of human resource competence, banking service quality and banking technology to customer satisfaction and the impact on customer behavior based on customer relationship management (CRM) performance. The test statistic used is designing the structural model, designing a measurement model, construct the path diagram, test the model fit. Suitability test structural models and hypotheses using software LISREL 8.80. The results showed that human resource competence, banking service quality and banking technology have a significant effect on customer satisfaction. And customer satisfaction have a significant effect on customer behavior based on customer relationship management (CRM) Performance.